Viral pneumonia in preschool children: current aspects of clinical and paraclinical diagnosis and treatment - S.O. Mokia-Serbina; T.V. Litvіnova; V.A. Shelevytska; N.I. Zabolotnia (Zaslavsky O.Yu., 2024)
Background. The article deals with the relevant problems of infectology pediatrics - viral pneumonias. Viral infections can be the cause of numerous disorders of the body, but respiratory complications are the most common, especially in preschool children. The purpose is to present the clinical and paraclinical features and treatment of pneumonia caused by common viral pathogens in preschool children based on a generalization of the available literature. Materials and methods. Modern domestic and foreign literary sources on clinical and paraclinical diagnosis and treatment of pneumonia caused by common viral pathogens were reviewed and analyzed. Web of Science, Scopus, PubMed, Google Scholar databases were studied to search for literature sources. When determining the recommendations, a new, 11th revision of the International Classification of Diseases and the results of prospective and retrospective studies conducted in recent years were taken into account. Results. Modern epidemiological and etiological data on viral pneumonias in children are presented, their terminology base is updated, which contributes to the consolidation of this diagnosis in pediatric practice. In the context of the problem, based on the analysis of the results of a multicenter retrospective examination, differences in clinical manifestations, laboratory parameters, and imaging results in pneumonia caused by common viral pathogens are presented. Clinical predictors for the presence of mycoplasma co-infections and secondary bacterial infection are highlighted. Wider implementation of modern methods of etiological diagnosis is recommended because of the risk of a high rate of co-infections in children with viral pneumonia. The issue of pneumonia treatment in preschool children is considered. Conclusions. The results of the analysis justify the existence of a significant dependence between the types of the pathogen and the features of viral pneumonia course in preschool children, increase the effectiveness of differential diagnosis in various clinical phenotypes and the assessment of laboratory activity of the disease. These data, with a high degree of probability, can ensure the choice of the optimal initial therapy, predict the disease course, and solve the issue of the need for hospitalization.